Perianal Crohn Disease Is More Common in Children and Is Associated With Complicated Disease Course Despite Higher Utilization of Biologics: A Population-based Study From The epidemiology group of the Israeli IBD Research Nucleus (epiIIRN). Issue 6 (22nd June 2022) - Atia, Ohad; Focht, Gili; Lujan, Rona; Ledder, Oren; Greenfeld, Shira; Kariv, Revital; Dotan, Iris; Yanai, Henit; Gabay, Hagit; Balicer, Ran; Haklai, Ziona; Nevo, Daniel; et al.
ABSTRACT: Background and Objectives: Both perianal and pediatric-onset Crohn disease (CD) disease are associated with complicated disease course and higher drug utilization. we aimed to explore the differences between pediatric and adult-onset perianal CD and their disease course. Methods: We included all patients with newly diagnosed CD from 2005 to 2019 at two Israeli Health Maintenance Organizations, covering 78% of the population. A combination of ICD-9 codes, radiology and procedures was used to define fistulizing perianal CD (PCD) and its severity according to the association with simple and complex perianal disease. Results: A total of 12, 905 patients were included (2186 [17%] pediatric-onset, 10, 719 [83%] adults), with a median follow-up of 7.8 years. PCD was diagnosed in 1530 (12%) patients, with higher incidence in children (308 [14%] children vs 1222 adults [11%]; P   <  0.001). Children had higher incidence of severe PCD (141/308 [47%] vs 433/1222 [35%]; P  < 0.001). At 5 years, children with PCD were more likely than adults to be treated with biologics (212 [69%] vs 515 [42%]; odds ratio [OR] 2.6 [95% confidence interval (CI) 1.6–4.0]; P < 0.001) and immunomodulators (238 [74%] vs 643 [53%]; OR 2.8 [95% CI 2.1–3.6]; P  < 0.001). PCD in children was still associated with poorer disease outcomes as shown for surgeries (36 [12%] vs 93 [8%]; P  = 0.02) and steroid-dependency (52 [17%] vs 156 [13%]; P  < 0.001). Multivariable modeling indicated that the severity of PCD is a stronger predictor of disease course than age. Conclusion: PCD is more common in pediatric-onset CD and is associated with higher drug utilization and worse disease outcomes, in large due to higher rate of severe PCD in children.